Objectivity, Prescription, Harmlessness, and Drudgery: Reflections of Lexicographers in Slovenia - Vrbinc, Alenka; Farina, Donna M.T.Cr.; Vrbinc, Marjeta (Lexikos, 2018)
This contribution reports on a study that set out to paint as complete a picture as possible of the context and content of modern Slovenian lexicography. We aimed to discern the philosophical underpinnings, the most noteworthy accomplishments, and the main projects of Slovenian dictionary work as presented by our seven subjects, who are all prominent members of the lexicographic community. We sought specialists who work on synchronic topics and concentrate more on the standard language and terminology rather than on dialectal variation and other lexicographic topics that are of more interest to scholars than to educated lay persons. The interview script consisted of thirteen narrative questions, designed to allow the interviewees to reflect in as much depth as possible on their daily practice as well as on their underlying vision of what lexicography or terminography is. This article discusses the development and influences of Slovenian lexicographic theory and presents part 1 of the results of this study: the views of the practicing lexicographers on whether they perceive their lexicographic work as drudgery and what they see as the essential nature of their role in society — how the dictionary maker can be a force for good and avoid any potential for harm.